If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4s + 13 = 29 Reorder the terms: 13 + 4s = 29 Solving 13 + 4s = 29 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 4s = 29 + -13 Combine like terms: 13 + -13 = 0 0 + 4s = 29 + -13 4s = 29 + -13 Combine like terms: 29 + -13 = 16 4s = 16 Divide each side by '4'. s = 4 Simplifying s = 4
| 8-4i/14i | | -6=x/12 | | -3x+5=-19 | | 1-5i/5+i | | 2x-1=97 | | (3p-8)/12=p/5 | | 3x+4=2x+2(x-7) | | (4x+1)(x-5)=0 | | (3p-8)/12=p/8 | | x^2(2x+3)=0 | | 0.5m+3=5 | | x(5x+3)=0 | | 3p-8/12=p/5 | | 5(3x+5)-12x=24 | | 14b^2-23b-15=0 | | 6x^2+7x=10 | | -4x+12.5=0.25x+4 | | 6x^2+x=10 | | 6x^2-29x-35=0 | | 4x-7=32x+14 | | 2x(x+3)(x-4)=0 | | y/9=6 | | 9x^2(x+4)=0 | | Y=3lnx | | .15X-3.2=1.3 | | -9+6=-18+3y | | 8a+5=5(3a-2)+1 | | 8/20-1/20 | | 5(x+6)-7=13 | | n-13=30 | | 7x^2(x+2)=0 | | -s+3= |